IBakti Siswa 1Malaysia (GBS1M) - Najjahul Huda, Hassan (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
1-2 December 2012. The first event of its kind, Gerak Bakti Siswa 1Malaysia (GBS1M), was jointly organised by the Centre for Modern Languages & Human Sciences (CMLHS), Universiti Malaysia Pahang (UMP) and Majlis Aspirasi Pemangkin Nasional (MAPAN). The two-day programme was supported by the East Coast Economic Region Development Council (ECERDC), and aimed to impart positive values and culture among university students and local community. In between it intended to promote the spirit of volunteerism among university students and to inculcate social values into practice.